Tourist Arrivals in India: How important are Domestic Disorders - Richa Dhariwala
The awareness among the people has increased tremendously owing to the rapid advancements in information and communication technologies. The international tourist arrivals have been used to proxy the international community's reaction to internal conflicts pertaining to India. Tourism industry not only reflects the opinion of outside communities but also strengthens the ties between different nations. This paper attempts to analyse empirically the determinants of international tourist arrivals in India using annual data from 1966 to 2000. The results document that socio-political factors, viz. communalism, terrorism and Indo-Pak tensions place serious threats to the tourism industry putting limits on the gains that could have been potentially realized. The losses that can be attributed to these conflicts have also been computed. Finally, some policy conclusions have been given to ensure internal peace and promote harmony between the two nations (in our case, India and Pakistan).